2018
DOI: 10.1016/j.joca.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

In thumb base osteoarthritis structural damage is more strongly associated with pain than synovitis

Abstract: Ultrasonographic and MRI inflammatory features were often present in the thumb base. Osteophytes were more strongly associated with thumb base pain than inflammatory features, in contrast to findings in finger OA studies, supporting thumb base osteoarthritis as a distinct phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 30 publications
2
39
5
Order By: Relevance
“…Several previous studies focused on the association between X-ray scores and pain in patients with CMC-1 OA. However, different methods are available to score X-rays [35] and the available literature is conflicting [6,7,[36][37][38][39]. Several radiographic OA features including erosions and sclerosis have been linked to pain levels [36,39], while Dahaghin et al [7] in a large population study (n ¼ 3906) reported that radiographic OA was poorly correlated with pain.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies focused on the association between X-ray scores and pain in patients with CMC-1 OA. However, different methods are available to score X-rays [35] and the available literature is conflicting [6,7,[36][37][38][39]. Several radiographic OA features including erosions and sclerosis have been linked to pain levels [36,39], while Dahaghin et al [7] in a large population study (n ¼ 3906) reported that radiographic OA was poorly correlated with pain.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also demonstrated that MRI is a reliable and reproducible method for detecting HOA changes in the interphalangeal joints [23] and thumb base first carpometacarpal joint [30]. Interestingly, in thumb base OA, structural damage was more strongly associated with pain than synovitis [30].…”
Section: Correlation Of Mri Changes With Plain Radiographymentioning
confidence: 94%
“…The mean age for all studies was 64.4 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Most studies (n = 13) were performed on both genders, although the majority of the subjects in each study were female.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations